(untitled) (Nigerian Journal of Pharmaceutical Research, 2025)
Background: Information on the interplay between gastric iNOS and COX-2 expression by Cobalt (CoCl2) during gastro-protection is unclear. Objective: Cobalt activities on iNOS and COX-2 interplay was investigated using Reserpine (RGU), and Pyloric-ligation (PLGU) gastric ulcer models. Materials and Methods: In RGU, 50 Wistar rats grouped; 1-control, 2-ulcerated untreated (RUU), 3, 4, and 5 were ulcerated pre-treated with 62mg/kg, 25mg/kg CoCl2 and 3.6mg/kg omeprazole for 5 days and sacrificed 3 and 8 hours after reserpine administration. In PLGU, 25 Wistar rats grouped; A-25mg/kg Cocl2, B-62mg/kg Cocl2, C-Cimetidine (36.88mg/kg), D-ulcerated untreated (UU), and E–control, were pretreated for 8 days prior 18 hours pyloric-ligation. Thereafter, macroscopic gastric ulceration (GU), biochemical analysis with histology, and immunohistochemistry were evaluated on excised stomach. Data were expressed as Mean+SEM, and p<0.05 was significant. Results: In RGU model, significant increase in GU score, nitric oxide, lipid peroxidation, and degranulated mast cells but a decrease in sulfhydryl, hydrogen peroxide levels in RUU by 3H and 8H were ameliorated by CoCl2. Histology revealed increased degranulated mast cells in the RUU compared with CoCl2-treated groups. CoCl2 treatment significantly decreased gastric acid secretion, ulcer index, parietal cell count, H+/K+ATPase and Na+/K+ATPase activities compared with UU. Gastric sulfhydryl, mucin, pepsin, with mucous cell count significantly increased in CoCl2-treated groups compared with UU. Gastric iNOS positive reactivity was upregulated while COX-2 positive reactivity was downregulated in CoCl2-treated groups compared with UU . Conclusion: Cobalt chloride exerted gastrointestinal cytoprotective action via mast cell stabilization, mucus production, with modulated expressions of gastric iNOS and COX-2 reactivity at the ulcerated site.